Surgical lifting - Khorasani, Hooman; Levit, Eyal; Dover, Jeffrey S.; Alam, Murad (Philadelphia, Pa. : Elsevier, 2024)
The book offers a step-by-step, practical approach to effective scar treatment, helping clinicians minimize the physical, aesthetic, and psychological impact of scarring. Edited by leading experts Drs. Jessica G. Labadie, Murad Alam, and Jeffrey S. Dover, it covers medical, surgical, and minimally invasive techniques, as well as lasers and energy-based devices. Provides clear, practical guidance on scar prevention and treatment, including acne, traumatic, burn, keloid, and hypertrophic scars. Features tips, pitfalls, and treatment algorithms for optimizing outcomes. Includes abundant illustrations, case studies, and new videos demonstrating laser and energy-based procedures.
Obsahuje kód s prístupom ku e-knihe
Obsahuje bibliografie a register
Evidence-based, hands-on resource designed for dermatologists, plastic surgeons, and other clinicians involved in scar management.
Keywords: výkony chirurgické dermatologické; tvár -- anatómia a histológia -- chirurgia; plastika tváre; omladenie; blefaroplastika; techniky kozmetické; chirurgia plastická; monografia